Pengaruh Pengembangan Sumber Daya Aparatur Terhadap Kinerja Aparatur Biro Hukum dan Ham Setda Provinsi Sulawesi Selatan - Saharuddin, S; Jafar, Sahari (Doktor Ilmu Manajemen, Universitas Muslim Indonesia, 2024)
The results of this study indicate that all variables, namely: education, training and career development have a positive and significant influence simultaneously on the performance of Apparatus Bureau of Law and Ham Setda South Sulawesi Province. Partially found that career development factor that has the most dominant significant influence on the performance of Apparatus Bureau of Law Dan Ham Setda South Sulawesi Province.